Strategy for Collecting Zakat Infaq Shadaqah at the Amil Zakat Infaq Shadaqah Muhammadiyah Institution (LAZISMU) Central Java Post Covid-19 Pandemic - Ridwan, Mohammad; Sriyono, Sriyono; Suharto, Sulistyo; Putri, Anindya P. R. Z. (Jurnal Ilmiah Ekonomi Islam, 2024)
The Covid-19 pandemic has had an impact on all areas of life and one of them is the field of zakat, due to the weak economy of the community due to the decline in income of Muzakki (people who are obliged to pay zakat), and on the other hand there has been an increase in Mustahik (people/entities who are entitled to receive zakat). This research aims to identify strategies for collecting zakat, infaq and shadaqah (ZIS) at the Muhammadiyah amil zakat, infaq and shadaqah institutions (LAZISMU) in the era of the covid-19 pandemic and after, apart from that, it also examines the extent of the impact of the post-covid-19 pandemic on ZIS zakat, infaq and shadaqah collection strategy at LAZISMU in the post-covid-19 pandemic era in Central Java. This research method is descriptive qualitative. Data collection techniques through observation, interviews, photos/videos, reports/subject documents. Meanwhile, the data analysis technique uses SWOT. The results of research conducted show that LAZISMU has a total weighted score of 3.78, while on the EFE matrix LAZISMU has a total weighted score of 3.67. LAZISMU's position is an above average position, so that in this position LAZISMU still has enough potential to be developed, however, it is also not recommended to develop strategies that are too aggressive, such as integration or acquisition strategies. In this position the company only needs to focus on maintaining, maintaining and improving its performance